MoS2 nanoflowers and PEDOT:PSS nanocomposite enabling wearable dual-mode pressure sensors - Wang, FengMing; Yang, WeiJia; Ma, Ke; Shen, GengZhe; Su, DaoJian; Li, BaiJun; Wang, ShuangPeng; Qin, BoLong; Zhang, Chi; Xin, Yue; Cao, XiaoBing; He, Xin (Science China. Technological sciences, 2024)
A versatile sensing platform employing inorganic MoS 2 nanoflowers and organic poly(3,4-ethylene dioxythiophene): poly (styrene sulfonate) (PEDOT:PSS) has been investigated to develop the resistive and capacitive force-sensitive devices. The microstructure of the sensing layer heightens the sensitivity and response time of the dual-mode pressure sensors by augmenting electron pathways and inner stress in response to mechanical stimuli. Consequently, the capacitive and resistive sensors exhibit sensitivities of 0.37 and 0.12 kPa −1 , respectively, while demonstrating a remarkable response time of approximately 100 ms. Furthermore, it is noteworthy that the PEDOT:PSS layer exhibits excellent adhesion to polydimethylsiloxane (PDMS) substrates, which contributes to the development of highly robust force sensitive sensors capable of enduring more than 10000 loading/unloading cycles. The combination of MoS 2 /PEDOT:PSS layers in these dual-mode sensors has shown promising results in detecting human joint movements and subtle physiological signals. Notably, the sensors have achieved a remarkable precision rate of 98% in identifying target objects. These outcomes underscore the significant potential of these sensors for integration into applications such as electronic skin and human-machine interaction.